Description of Workforce Preparedness for Fire Management at Dinoyo Health Center - Fresvian Jenrivo; Ani Asriani Basri; Fariz Zuvil Arganata; Zanuba Syifa' Qotrunnada (Universitas Muhammadiyah Malang, 2024)
Background: Dinoyo Community Health Center is a health facility in Malang City that must implement fire safety. There have been 4 incidents in 2020 and 8 incidents in 2021 where fire occurred at community health centers. Preparedness is carried out as an effort to deal with fires from a human perspective. Research objective: To determine workforce preparedness for fire management at the Dinoyo Community Health Center. Research type: descriptive quantitative with a population of 55 people using saturation sampling techniques. There are 2 preparedness parameters in this research variable, namely knowledge and attitudes. Results: The preparedness of the workforce is